The influence of Premium Insurance and Sales Distribution Method on Customer Buying Decision (A case study at PT Asuransi Allianz Utama Indonesia Semarang Branch) - Scarleta - Dayu; Suryadi - Poerbo; Erika - Devie (Politeknik Negeri Semarang, 2020)
This research aims to explain the influence of premium insurance and sales distribution method on customer buying decision of marine insurance in PT Asuransi Allianz Utama Indonesia Semarang Branch. The independent variables used in this study were premium insurance and sales distribution method, while the dependent variable was customer buying decision. The methods of data collection used in this study were literature studies and questionnaires with 38 samples. The analysis results from this research showed that both premium insurance and sales distribution method had significant and positive effect on customer buying decision partially and stimulously. The value of t count in premium insurance was greater than t table (2.564 > 2.03011) with significant value 0.015 < 0.05 and the value of t count in sales distribution method was also greater than t table (5.140 > 2.03011) with significant value of 0.00. The F test stated that both premium insurance and sales distribution method simultaneously had a significant effect on customer buying decision. It was indicated with significant value of 0.000 < 0.05 and the value of F count > F table (36.225 > 4.110). This study shows premium insurance and sales distribution methood were able to contribute on customer buying decision by 67.4% and the remaining 32.6% influenced by other variables not examined in this research.